Analysis of Locutionary Acts in the Novel Arsana di Balik Jendela Kaca by A.C. Agni (Pragmatic Study) - Sri Hastuti (Proceeding of the International Conference on Global Education and Learning, 2025)
Speech acts are one aspect of pragmatic studies. Speech acts are divided into several forms, one of which is locutionary. Locutionary act is a speech act performed by the speaker to convey something. The purpose of this study is to describe locutionary speech acts in the novel Arsana Behind the Glass by A.C. Agni. The type of research used is descriptive qualitative. The source of data in this study is Arsana's Novel Behind the Glass Window. The data collection technique used was document study with the researcher as the key instrument. Test the validity of using triangulation theory and persistence of researchers. The data analysis technique is content analysis. Based on the research, it can be concluded that the locutionary speech acts contained in the novel are directive, interrogative, and imperative. Practically the results of this study can help to understand speech acts in pragmatic studies.